Financial Incentives and the Timing of Retirement: Evidence from Switzerland - Barbara Hanel; Regina Riphahn (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
We use reforms in the Swiss public retirement system to identify the responsiveness of retirement timing to financial incentives. A permanent reduction of retirement benefits by 3.4 percent induces more than 70 percent of females to postpone their retirement. The responsiveness of male workers, who undergo a different treatment, is lower.
Keywords: J26; H55; J14; 330; retirement insurance; incentives; social security; labor force exit; natural experiment; Switzerland